Repeat Migration in the Age of the "Unauthorized Permanent Resident": A Quantitative Assessment of Migration Intentions Postdeportation. Issue 4 (December 2018) - Martínez, Daniel E.; Slack, Jeremy; Martínez-Schuldt, Ricardo D.
Drawing on postdeportation surveys ( N = 1, 109) with Mexican migrants, we examine the impact of immigration enforcement programs and various social factors on repeat migration intentions. Our multivariate analyses suggest immigrants with strong personal ties to the United States have higher relative odds of intending to cross the border again, even when controlling modes of removal from the United States. Our findings highlight the inevitable failure of immigration policy and enforcement programs when placed against the powerful pull of family and home. These findings shed greater insight on the complex nature of unauthorized migration in an era of increased securitization and deportation.